Spatial processes dominate the metacommunity structure and diversity of macroinvertebrates in the waters of eastern China - Zheng, Biao; Tian, Shuang; Sun, Bingjiao; Gao, Xin; Han, Wennuo; Wu, Bin; Hu, Sheng; Li, Zhao (Frontiers in Ecology and Evolution, 2024)
The emergence of metacommunity theory has provided a framework for studying the spatial structure of biological communities. To unravel the underlying driving mechanisms of macroinvertebrate metacommunity structure and diversity, this paper evaluates macroinvertebrate data from a water body in eastern China using variance decomposition and stratified partitioning. The results suggest that spatial processes dominate macroinvertebrate metacommunity structure, while the combined effects of spatial processes, aquatic environment, and geoclimatic factors also explain part of the macroinvertebrate community structure. Spatial processes, aquatic environment, and geoclimatic factors significantly influenced macroinvertebrate alpha diversity and indirectly influenced beta diversity through alpha diversity. Therefore, the significant effects of spatial processes and geoclimatic variables cannot be ignored in biological assessments, especially biodiversity assessments. Our findings elucidate the metacommunity dynamics in the region and provide crucial information for conservation planning in riverine ecosystems.